2019
DOI: 10.3390/toxics7030047
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Fluorine Release from Photovoltaic Backsheet Materials Containing PVF and PVDF during Pyrolysis and Incineration in a Technical Lab-Scale Reactor at Various Temperatures

Abstract: With a sharp increase in photovoltaic (PV) installations across the world, PV waste is now a relatively new addition to the e-waste category. From 45,000 tonnes in 2016, the PV waste stream is rapidly increasing and is projected to reach 60 million tonnes by 2050. Backsheets are composite structures made from several material layers of polymer, adhesive, and primer. Widely used PV backsheets can be classified into three core types: (a) KPK (Kynar®/polyethylene terephthalate (PET)/Kynar®), (b) TPT (Tedlar®/PET/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Those conclusions align well with the back sheet only representing 2.8 to 3.5% of the module weight, whereas the encapsulate represents 6.3 to 8% [55]. The two highly thermally stable fluoropolymers Tedlar and Kynar are among the most used products for back sheets [55,56] and with a heat of combustion between 4.1 kJ/g and 5.4 kJ/g [57], a very limited additional heat flux was expected. In contrast, the heat of combustion of the commonly used encapsulate ethyl vinyl acetate (EVA) [55] is 41.6 kJ/g [58] and despite previous research indicating that the contribution is limited, it does, theoretically, increase the fire load on the roof.…”
Section: Panelssupporting
confidence: 69%
“…Those conclusions align well with the back sheet only representing 2.8 to 3.5% of the module weight, whereas the encapsulate represents 6.3 to 8% [55]. The two highly thermally stable fluoropolymers Tedlar and Kynar are among the most used products for back sheets [55,56] and with a heat of combustion between 4.1 kJ/g and 5.4 kJ/g [57], a very limited additional heat flux was expected. In contrast, the heat of combustion of the commonly used encapsulate ethyl vinyl acetate (EVA) [55] is 41.6 kJ/g [58] and despite previous research indicating that the contribution is limited, it does, theoretically, increase the fire load on the roof.…”
Section: Panelssupporting
confidence: 69%
“…A c-Si absorber layer (6 wt %) is connected by Pb-coated Cu wires and Ag grid wires on the front, while Al is on the back for current transfer. , The front layer is usually made of glass, and the back sheet (0.8 wt %) comprises polymers, fluorinated polymers such as polyvinyl fluoride (Tedlar), polyvinylidene fluoride, or ethylene chlorotrifluoroethylene . The back sheet is widely of three types, (a) KPK (PET/Kyner), (b) TPT (PET/Tedler), and (c) PPE (PET/EVA), and comprises C (54.9%–63.8%), H (4.3%–6.6%), O (24.5%–30.5%), N (0.2%), and F (0–9%) . The average composition of c-Si entails 75%–80% glass (front layer), 10% polymer (encapsulant and back sheet, SiN x ), 10% Al (mostly frame), 3%–5% Si (solar cells), and 1% Cu (connectors) .…”
Section: Solar Cell: Types and Structurementioning
confidence: 99%
“…While no flue gas characterization has been performed in this work, this topic is of high importance and is therefore discussed briefly. Danz et al (2019) have shown that F-containing backsheets (containing PVF or PVDF) release notable amounts of fluorine (mostly in the form of hydrofluoric acid) when subjected to a thermal process. Detrimental effects on the environment and human health are expected if these emissions are handled incorrectly.…”
Section: Output Characterizationmentioning
confidence: 99%